"Suddenly, bang, one day there's commitment with a woman…" Men, vasectomy and the life course. (September 2014) - Terry, Gareth
Abstract Research that investigates and theorises the male reproductive life course is extremely limited, and often reduced to examining problems, such as infertility. As a consequence, what we know about men's reproductive decision making is often extrapolated from theorisation of the female reproductive life course, or simplistic assumptions about masculine identity. This article analyses interview data from 34 men talking about their vasectomy decision-making processes in order to provide a lens through which to understand men making sense of their reproductive life course. Men who had children spoke of their vasectomy as resolving their lay understandings of the 'normal' life course, men who did not want their children to speak of resisting the normal life course, and men who had experienced or considered relationship dissolution spoke of resetting the life course.